A study of the relationship between total quality management and business performance in the banking sector. (11th December 2020) - Tagger, Sukhjinder Singh; Gupta, Munish
Total quality management (TQM) is a buzz word of the modern business. In the recent years, the manufacturing as well as service sectors have widely used the philosophy of total quality management with the aim to provide quality service to the customers and exceed their expectations. The present study aims at studying the relationship between the total quality management and business performance in the banking sector. The findings of the study done on the banking sector revealed that the quality of service, focus on customers, teamwork and environment greatly dominated and influenced the performance of banks. Other factors were also identified which directly or indirectly influenced the business performance of banks. The present study shows how the philosophy of TQM is relevant in the banking sector to enhance the customer satisfaction through better service quality. It also helps the banks to understand the needs and expectations of the customers better. The banks need to implement the key TQM factors successfully to get the enhanced performance.